SISTEM PEMIDANAAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Salman Paris Harahap; Madiasa Ablisar; Marlina Marlina; Suhaidi Suhaidi (USU LAW JOURNAL, 2018)
ABSTRACT Children  as criminals must be treated humanely to the best interests of the child to realize growth and provide physical, mental and social. The protection of children is also reflected in the provisions of Article 28 and paragraph (2) of the 1945 Constitution the basic rights of children, that "every child has the right to live, grow and develop and is entitled to protection from violence and discrimination". In the provisions of Law No. 11 of 2012 on the Criminal Justice System Child, that the system of punishment against juvenile offenders under the law is more emphasis on educational punishment for the best interests of the child. Therefore, this paper attempts to examine the criminal system of children as perpetrators of criminal acts in Indonesia and to analyze the criminal system of children according to Law No. 11 of 2012 on the Criminal Justice System Child and criminal system of children according to Islamic law and criminal system that is managed by Act No. 11 of 2012 on the criminal Justice System children in addressing offenses in doingchild.The method used in this research is normative juridical research method with the approach taken is the approach of legislation (statute approach). Legislation approach used for the basic criminal system that is used as the subject of this research is the Law No. 11 Year 2012 on Child Criminal Justice System. It also conducted a comparative approach (comparative approach).The results showed that the criminal system in Indonesia at this time referring to the Law No. 11 of 2012 concerning juvenile justice system that provisions are required in trying to do a restorative justice (restorative justice) and diversion. Child criminal system according to Law No. 11 of 2012 on the Criminal Justice System Child by child criminal system according to Islamic law lies in the concept of criminal responsibility, it can be seen from the constraints of a child is able to take responsibility. Analysis of Law Number 11 Year 2012 on Child Criminal Justice System is a system of punishment is more emphasis on restorative justice. For children as criminals, where the sanction is not the main goal for the criminalization of children because imprisonment is ultimum remedium.   Keywords: criminal system, children in conflict with the law, criminal justice system children.